The Effect of Sabit Kick Training Program with High Intensity Interval Training (HIIT) on Speed and Agility - Fitriana Putrie, Sofhia; Sumartiningsih, Sri (Journal of Physical Education and Sports, 2025)
The sabit kick, a crucial technique in pencak silat, is a high-scoring attack in competitions, where speed and agility play key roles in its effectiveness. However, many athletes struggle to achieve optimal speed due to a lack of training programs to enhance muscle explosiveness and motor response. This study aims to analyze the effect of High-Intesity Interval training (HIIT) on the speed and agility of sickle kicks for pencak silat athletes. The study metod was a quasi-experiment with one group with a pre-test and post-test design, involving 20 athletes from pagar nusa who college underwent 12 training sessions in one month, training the Speed, Agility and Quickness (SAQ). A combination of Tabata Speed and data was collected through a 20-meter sprint test, Illinois agility test, and kick speed measurements before and after the intervention. The analysis result with paired sample t-test showed a significant increase (p < 0.05) in sickle kick speed and agility after HIIT. The study concludes that HIIT effectively enhances th eperformance of pencak silat athletes, particulary in speed and agility. These findings suggest that coaches should incorporate HIIT into training programs and encourage further research to determine the optimal duration and intensity for improving fighting techniques.